Cisplatin-Based Chemotherapy versus Cetuximab in Concurrent Chemoradiotherapy for Locally Advanced Head and Neck Cancer Treatment. (6th July 2014) - Hu, Ming-Hung; Wang, Ling-Wei; Lu, Hsueh-Ju; Chu, Pen-Yuan; Tai, Shyh-Kuan; Lee, Tsung-Lun; Chen, Ming-Huang; Yang, Muh-Hwa; Chang, Peter Mu-Hsin
Abstract : Background and Purpose . This study aimed to analyze survival, clinical responses, compliance, and adverse effects in locally advanced head and neck cancer (LAHNC) patients treated with split-dose cisplatin-based concurrent chemoradiation therapy (SD-CCRT) or cetuximab with concurrent radiation therapy (BioRT). Materials and Methods . We retrospectively evaluated 170 LAHNC patients diagnosed between January 1, 2009, and July 31, 2012: 116 received CCRT and 54 received BioRT. Results . Complete response rates were similar in the SD-CCRT and BioRT groups (63.8% versus 59.3%; P = 0.807 ), and locoregional relapse rates were 18.1% and 13.0%, respectively (P = 0.400 ). The 3-year relapse-free survival rate was 65.8% in the SD-CCRT group and 65.5% in the BioRT group, respectively (P = 0.647 ). The 3-year overall survival rate was 78.5% in the SD-CCRT group and 70.9% in the BioRT group, respectively (P = 0.879 ). Hematologic side effects were significantly more frequent in the SD-CCRT than in the BioRT group. Mucositis frequency was similar. Conclusions . Primary SD-CCRT and BioRT both showed good clinical response and survival. Hematologic toxicities were more frequent, but tolerable, in the SD-CCRT group. Both groups showed good compliance.